Confirming, Classifying, and Prioritizing Needed Over-the-Bed Table Improvements via Methodological Triangulation. (October 2014) - Manganelli, Joe; Threatt, Anthony; Brooks, Johnell O.; Healy, Stan; Merino, Jessica; Yanik, Paul; Walker, Ian; Green, Keith
OBJECTIVE: This article presents the results of a qualitative study that confirmed, classified, and prioritized user needs for the design of a more useful, usable, and actively assistive over-the-bed table. BACKGROUND: Manganelli et al. (2014) generated a list of 74 needs for use in developing an actively assistive over-the-bed table. This present study assesses the value and importance of those needs. METHODS: Fourteen healthcare subject matter experts and eight research and design subject matter experts engaged in a participatory and iterative research and design process. A mixed methods qualitative approach used methodological triangulation to confirm the value of the findings and ratings to establish importance. Open and closed card sorts and a Delphi study were used. Data analysis methods included frequency analysis, content analysis, and a modified Kano analysis. RESULTS: A table demonstrating the needs that are of high importance to both groups of subject matter experts and classification of the design challenges each represents was produced. Through this process, the list of 74 needs was refined to the 37 most important need statements for both groups. CONCLUSIONS: Designing a more useful, usable, and actively assistive over-the-bed table is primarily about the ability to position it optimally with respect to the user for any task, as well as improving ease of use and usability. It is also important to make explicit and discuss the differences in priorities and perspectives demonstrated between research and design teams and their clients.